NEPAD and Right to Development in Africa: A Critical Review - Ojo-Lanre , Temiloluwa Anne; Amodu, Akeem (Kashere Journal of Politics and International Relations, 2024)
Right to Development is universally enshrined by the United Nations as every individual is entitled to participate in, contribute to, and benefit from the process of development. Thus, NEPAD was created to help achieve this purpose under the framework of the African Union. However, amidst the creation of economic plans and unit by the African Union which is meant to help in the attainment of Right to Development in Africa, Rights to Development is yet to be achieved and attained as the set goals and objectives of these economic plans and units are yet to be achieved. The research paper thereby investigates NEPAD’s impact and prospect on Right to Development. While the research paper adopts a qualitative approach that involves the use of secondary data sources such as academic journals, government reports, media reports, and library sources, the paper finds NEPAD has contributed to enhancement of Right to Development in Africa by strengthening good governance in the continent as well as improved education and skills in the continent. The paper concludes that NEPAD (New Partnership for Africa’s Development) is an important initiative that has been implemented in Africa amidst the challenges it faces. The study recommends dialogue and collaboration among member states to share experiences, challenges, and lessons learned in promoting the right to development within their respective contexts and strengthening collaboration between NEPAD and civil society organizations to enhance transparency, accountability, and public participation in development initiatives.